Unearthing the Cultural Meanings of Burial Rituals: A Comparative Discourse on the New Testament and amaXhosa Traditions - Diko, Mlamli (Journal of early Christian history, 2025)
Burial rituals have historically been cultural reflections which represent belief systems about life, death, and the afterlife, and serve as profound tapestries woven with the threads of existential meaning. In this article, I scrutinise the cultural meanings of burial rituals, comparing the New Testament’s focus on rebirth or resurrection and eternal life with the amaXhosa traditions’ emphasis on ancestral recognition, reverence, and communal identity. The focus of the article is not on the entire New Testament (NT) text, but on selected contexts. Applying symbolic interactionism, I uncover how these practices function as cultural artefacts, reflecting multi-collaborative and divergent constructions of life, death, and the spiritual kingdom. Three notable findings emerge. First, while certain biblical texts in the NT concentrate on individual standing with God, amaXhosa traditions foreground collective obligation and continuity with the ancestors. Second, symbols such as the tomb in the NT discourse and animal slaughter in amaXhosa burial rituals convey multilayered yet complicated social values and theological imperatives. Third, both cultural contexts use burial spaces to cement cultural cohesion and consciousness, albeit through differing metaphysical experiences. Inevitably, by scrutinising these intersections and contrasts, this article unmasks the dynamic chemistry between religious doctrine and cultural heritage. Above all, this article is interdisciplinary, blending NT discourse, cultural philosophies, and amaXhosa traditions to establish how burial rituals, as cultural artefacts, signify diverse belief systems.